Essential Oil Rendemen Analysis of Nutmeg (Myristica fragrans) Seeds in Various Classes of Sunlight Intensity at Batu Keramat Village, Kota Agung Subdistrict, District of Tanggamus - Erin Agesta Ariandi; Duryat Duryat; Trio Santoso (Department of Forestry, Faculty of Agriculture, University of Lampung, 2018)
Nutmeg tree (Myristica fragrans) is a spice tree with high economic value. Nutmeg fruit was contains essential oil as the results of secondary metabolism process. Adequacy of sunlight, the average distance of intersect trees, the tree species and numbers of intersect trees on photosynthesis and the results of secondary metabolism. The aimed of the study was to analyze the rendemen yield obtained from the nutmeg fruit based on differences sunlight intensity with the differences stratum canopy and determine the factors that influence the yield of nutmeg essential oil. The differences of sunlight intensity was used as a treatment there were three classes of sunlight intensity which were low sunlight intensity (0-25%), the moderate sunlight intensity (25-75%) and the high sunlight intensity (75-100%). The multiple linier regression was employed as data analysis method. The result explained that the best sunlight intensity was the moderate (25-75%) with essensial oil rendemen as much 198,2 ml/kg. The result test F shown that in all variable (the sunlight intensity (X1), the average distance of intersect trees (X2), the tree species (X3) and numbers of intersect trees (X4)), significantly influened the production of essensial oil. The results of multiple linear regression analysis deliver the equation of Y = 2,133 + 0.037X1 + 0.275X2 - 0.226X3 - 0.049X4, the equation show a positive value means direcly proporsional to the result of yield by nutmeg essensial oil and a negative value means the opposite. 60,2% coeficient determination value, which means that the equation could explain 60,2% the variables influence to the nutmeg essensial oil rendemen. Keywords: essential oil, multiple linear regression, Myristica fragrans, sunlight intensity